Protein Z: A putative novel biomarker for early detection of ovarian cancer. Issue 12 (19th February 2016) - Russell, Matthew R.; Walker, Michael J.; Williamson, Andrew J. K.; Gentry‐Maharaj, Aleksandra; Ryan, Andy; Kalsi, Jatinderpal; Skates, Steven; D'Amato, Alfonsina; Dive, Caroline; Pernemalm, Maria; Humphryes, Phillip C.; Fourkala, Evangelia‐Ourania; et al.
Abstract : Ovarian cancer (OC) has the highest mortality of all gynaecological cancers. Early diagnosis offers an approach to achieving better outcomes. We conducted a blinded‐evaluation of prospectively collected preclinical serum from participants in the multimodal group of the United Kingdom Collaborative Trial of Ovarian Cancer Screening. Using isobaric tags (iTRAQ) we identified 90 proteins differentially expressed between OC cases and controls. A second targeted mass spectrometry analysis of twenty of these candidates identified Protein Z as a potential early detection biomarker for OC. This was further validated by ELISA analysis in 482 serial serum samples, from 80 individuals, 49 OC cases and 31 controls, spanning up to 7 years prior to diagnosis. Protein Z was significantly down‐regulated up to 2 years pre‐diagnosis ( p = 0.000000411) in 8 of 19 Type I patients whilst in 5 Type II individuals, it was significantly up‐regulated up to 4 years before diagnosis ( p = 0.01). ROC curve analysis for CA‐125 and CA‐125 combined with Protein Z showed a statistically significant ( p = 0.00033) increase in the AUC from 77 to 81% for Type I and a statistically significant ( p = 0.00003) increase in the AUC from 76 to 82% for Type II. Protein Z is a novel independent early detection biomarker for Type I and Type II ovarian cancer; which can discriminate between both types. Protein Z also adds to CA‐125 and potentially the Risk of Ovarian Cancer algorithm in the detection of both subtypes. Abstract : What's new? New biomarkers for the early detection of ovarian cancer (OC) are urgently needed. In this blinded, prospective study, the authors identified Protein Z as a novel early marker for Type I and Type II OC that can also discriminate between the two types. When Protein Z levels were combined with CA‐125, results for early detection were even better. They may also enhance the Risk of Ovarian Cancer algorithm. These findings should help researchers develop more sensitive and specific screening panels for early‐stage OC.